2012
DOI: 10.1002/btpr.1528
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time monitoring of shake flask fermentation and off gas using triple disposable noninvasive optical sensors

Abstract: Bioprocess development is a data-driven process requiring a large number of experiments to be conducted under varying conditions. Small-scale upstream bioprocess development is often performed in shake flasks because they are inexpensive and can be operated in parallel. However, shake flasks are often not equipped to accurately monitor critical process parameters such as pH, dissolved oxygen, and CO2 concentrations. Therefore, there is no definitive information on oxygen supply of growing cells, CO2 formation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The method was applied to monitor pH changes caused by the growth and metabolism of a culture of the pathogen Staphylococcus aureus. Rao and co-workers integrated optical pH sensors (hydrogel-immobilized 6,8-dihydroxypyrene-1,3-disulfonic acid or Dowex-immobilized HPTS) and oxygen sensors in (micro)bioreactors for mammalian cell culture, 100,394 cultivation of E. coli 380,1169,1170 and effective clone selection. 1171 Good agreement was found between values obtained by optodes and electrodes, respectively.…”
Section: Sensing and Imaging Of Ph Values In Biotechnologymentioning
confidence: 99%
“…The method was applied to monitor pH changes caused by the growth and metabolism of a culture of the pathogen Staphylococcus aureus. Rao and co-workers integrated optical pH sensors (hydrogel-immobilized 6,8-dihydroxypyrene-1,3-disulfonic acid or Dowex-immobilized HPTS) and oxygen sensors in (micro)bioreactors for mammalian cell culture, 100,394 cultivation of E. coli 380,1169,1170 and effective clone selection. 1171 Good agreement was found between values obtained by optodes and electrodes, respectively.…”
Section: Sensing and Imaging Of Ph Values In Biotechnologymentioning
confidence: 99%
“…To our knowledge, this is the first study to report that the CO 2 concentration increases (~85.0 mg/L) during shake-flask culture using a culture plug-capped Erlenmeyer flask, compared with the initial culture condition (~4.0 mg/L). A previous study has reported the monitoring of dissolved CO 2 in shake-flask culture (Ge and Rao 2012 ). However, this study focused on the development of a sensor for dissolved CO 2 and O 2 , and the pH in the flask was different from that at standard conditions of shake-flask culture (a milk filter and 2 L flask filled with 50 mL of medium).…”
Section: Discussionmentioning
confidence: 99%
“…Based on similar principles, a fiber‐optic sensor has been made for on‐line monitoring of dissolved CO 2 using pH sensitive dye entrapped in gas permeable membrane . In another design, a patch with a responsive layer of pH sensitive fluorophore can be affixed to the inside wall of the flask to measure CO 2 concentration in both gas and liquid phases .…”
Section: Sensors Commonly Used In Bioprocessmentioning
confidence: 99%